COMPARATIVE LEXICAL-SEMANTIC AND STRUCTURAL ANALYSIS OF UZBEK AND ENGLISH PROVERBS WITH RELIGIOUS AND SPIRITUAL COMPONENTS - Ismoilova Gulyora Xabibullo qizi (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Proverbs are an integral component of the linguistic and cultural heritage of any nation. As condensed expressions of collective wisdom, they encapsulate moral codes, social norms, and philosophical reflections in forms that are memorable and easily transmitted. When examined through the lens of religion and spirituality, proverbs reveal an even deeper layer of meaning, offering insights into the metaphysical beliefs, ethical values, and behavioral prescriptions of a given culture. In the context of Uzbek and English traditions, proverbs related to religion not only preserve centuries-old faith-based knowledge but also demonstrate the interplay between sacred teachings and daily human experience. This study seeks to conduct a comparative lexical-semantic and structural analysis of Uzbek and English proverbs with explicit and implicit religious elements, focusing on categories such as sin, repentance, good deeds, charity, judgment day, prayer, fasting, halal/haram, faith, and religious figures. The research addresses both denotative and connotative meanings while situating the findings within broader cultural and linguistic frameworks.